(untitled) (World Bulletin of Social Sciences, 2026)
This article analyzes the theoretical and pedagogical foundations of forming a methodology for integrating artificial intelligence into the primary education process through extracurricular activities. The study highlights the didactic potential of artificial intelligence tools in developing pupils’ cognitive activity, creative thinking, digital literacy, and independent working skills. It also scientifically explains the organizational forms, pedagogical conditions, and effectiveness factors of using these technologies in extracurricular activities. Their significance in innovative development is also evaluated.